IS BRAIN PLASTICITY A CRITICAL FACTOR IN THE TREATMENT OF COGNITIVE ALTERATIONS ASSOCIATED WITH AGING? - Redolat, Rosa; Carrasco, Mari Carmen (Anales de Psicología / Annals of Psychology, 1998)
In this paper we present a critical approach to one of the subjects of special interest in the ambit of neurosciences. Recent investigations have attempted to establish whether the modification and potentiation of brain plasticity could be of therapeutic benefit in the treatment of cognitive deficits related to normal aging and to neurodegenerative diseases such as Alzheimer´s disease. The question we try to answer is whether the cognitive decline could be ameliorated or even prevented with strategies based on the ability of the Central Nervous System for plasticity, an ability that is believed to be maintained until an advanced age. Our aim is to review the scientific evidence that seems to suggest that the answer to the question posed in the title of this paper could be affirmative in the sense that brain plasticity in response to several factors (health status, nutrition, physical activity, cognitive training…) would be a critical element in the achievement of a more healthy aging.